High oxidation rates from combined carbohydrates ingested during exercise - Jentjens, R. L.; Achten, J.; Jeukendrup, A. E. (Medicine & Science in Sports & Exercise, 2004)
Studies that have investigated oxidation of a single carbohydrate (CHO) during exercise have reported oxidation rates of up to 1 g x min(-1). Recent studies from our laboratory have shown that a mixture of glucose and sucrose or glucose and fructose ingested at a high rate (1.8 g x min(-1)) leads to peak oxidation rates of approximately 1.3 g x min(-1) and results in approximately 20 to 55% higher exogenous CHO oxidation rates compared with the ingestion of an isocaloric amount of glucose. PURPOSE: The purpose of the present study was to examine whether a mixture of glucose, sucrose and fructose ingested at a high rate would result in even higher exogenous CHO oxidation rates (>1.3 g x min(-1)). METHODS: Eight trained male cyclists (VO2max: 64 +/- 1 mL x kg(-1) BM x min(-1)) cycled on three different occasions for 150 min at 62 +/- 1% VO2max and consumed either water (WAT) or a CHO solution providing 2.4 g x min(-1) of glucose (GLU) or 1.2 g x min(-1) of glucose + 0.6 g x min(-1) of fructose + 0.6 g x min(-1) of sucrose (MIX). RESULTS: High peak exogenous CHO oxidation rates were found in the MIX trial (1.70 +/- 0.07 g x min(-1)), which were approximately 44% higher (P < 0.01) compared with the GLU trial (1.18 +/- 0.04 g x min(-1)). Endogenous CHO oxidation was lower (P < 0.05) in MIX compared with GLU (0.76 +/- 0.12 and 1.05 +/- 0.06 g x min(-1), respectively). CONCLUSION: When glucose, fructose and sucrose are ingested simultaneously at high rates (2.4 g x min(-1)) during cycling exercise, exogenous CHO oxidation rates can reach peak values of approximately 1.7 g x min(-1) and estimated endogenous CHO oxidation is reduced compared with the ingestion of an isocaloric amount of glucose.